Prevalencia de abuso infantil en una muestra de jóvenes universitarios/as Chilenos - Vizcarra Larrañaga, Beatriz; Balladares Gutiérrez, Eliana (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This article describes results from a study o prevalence o sexual abuse during childhood in a sample o 598 Chilean university students from the city o Temuco in Chile. The data collected through an anonymous, self-administered questionnaire revealed that 14.3% of the participants had “been involved in sexual experiences with older people.” Characteristics of abuser and abused as well as the circumstances of the abuse are described and they are compared with previous studies conducted in same context.